Effect of Dietary Incorporation of Moringa oleifera Leaf Meal on Growth Performance and Nutrient Utilization of Japanese Quail - Lata, Manju; Mondal, Bidhan C; Palod, Jyoti; Rahal, Anshu; Prabhakaran, P (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A feeding trial was conducted to discern the influence of dietary incorporation of Moringa oleifera leaf meal on growth performance and nutrient utilization of Japanese quail for 6 weeks. A total 288 day-old Japanese quail chicks were randomly distributed into eight treatments of 36 Japanese quail chicks per treatment with three replicates of 12 quail in each. Japanese quail of treatment T1 (control group) were fed a basal diet (starter and finisher), whereas in treatment group T2 basal diet was incorporated with Vitamin C @200 mg/kg, T3 basal diet was incorporated with Vitamin E @10 IU/kg, and in diets T4, T5, T6, T7, and T8, the basal diet was incorporated with 1.0%, 3.0%, 5.0%, 7.0% and 9.0% Moringa oleifera leaf meal, respectively. Results showed that incorporation of 3.0% Moringa oleifera leaf meal improved the performance of Japanese quail in terms of body weight gain and performance index during the overall period. The maximum crude protein utilization was seen in 3.0% Moringa oleifera leaf meal incorporated group of Japanese quail followed by 1.0%. However, maximum ether extract utilization was seen with 1.0% Moringa oleifera leaf meal while ether extract and crude protein utilization was lower in 9.0% Moringa oleifera leaf meal incorporated group. Average feed cost per kg weight gain differed in Japanese quail offered various dietary treatment. It can be concluded that 3.0 % Moringa oleifera leaf meal can be incorporated in feed for improvement in growth performance of Japanese quail.